The socialization of mexican political elites through corruption (2011)
This article focuses on the study of corruption as one of the factors influencing and facilitating the socialization of Mexican political elites in the context of political relations based on close friendship, family relations, caciquism or bossism, and patronage. It also analyzes the phenomenon of corruption as a factor in the process of political recruitment, mobility of elites and provides a scheme in the exercise of political power in Mexico.